TFIIA induces conformational changes in TFIID via interactions with the basic repeat. - Lee, D K (1992)
DNA-binding studies with Saccharomyces cerevisiae TFIID point mutants indicated that TFIIA interacts with the basic repeat region of TFIID and induces structural changes. The latter was shown by the ability of TFIIA to compensate for TFIID point mutants defective for DNA binding. Interaction with TFIIA also rendered TFIID binding temperature independent, thus mimicking the effect of removing the nonconserved N terminus of TFIID. In addition, N-terminal truncation of the TFIID point mutants defective for DNA binding mimicked the ability of TFIIA to restore DNA binding of those mutants. Taken together, these results suggest that TFIIA enhances TFIID binding to DNA by eliminating an otherwise inhibitory effect of the nonconserved N terminus of TFIID. Furthermore, analyses of TFIID contact points on DNA and binding studies with TATA-containing oligonucleotide probes showed that TFIIA decreases the effect of sequences flanking the adenovirus major late TATA element on TFIID binding to DNA, suggesting a possible role of TFIIA in allowing TFIID to recognize a wider variety of promoters.